Improving Learning Outcomes of Islamic Religious Education through the Think-Pair-Share (TPS) Learning Model for Grade 7 Students of SMPN 5 Satu Atap Kunto Darussalam - Supriyadi, Supriyadi; Nismar, Nismar; Jasrizal, Jasrizal (STKIP Rokania Pasir Pangaraian, 2024)
This research aims to improve the learning outcomes of Islamic Religious Education students in grade 7 of SMP Negeri 5 Satu Atap Kunto Darussalam by applying the Think-Pair-Share type cooperative learning model. The research method used is Classroom Action Research (PTK) with the Kemmis and McTaggart model, which consists of four stages: planning, action, observation, and reflection. The subject of the study was a 7th-grade student at a junior high school. Data was collected through learning outcome tests, observations, and interviews. The results of the study show that applying the TPS model can increase students' active participation in learning and improve their learning outcomes. In the first cycle, learning completeness reached 65%, while it increased to 85% in the second cycle. In conclusion, the TPS model effectively improves the learning outcomes of Islamic Religious Education students in grade 7 of SMP Negeri 5 Satu Atap Kunto Darussalam